Topaz [videorecording (DVD)] - Jarre, Maurice (Alfred Hitchcock collection., 2006)
The best-selling spy novel bursts onto the screen in this riveting story of adventure and international intrigue. An American CIA agent hires a French operative to travel to Cuba and intestigate rumors of Russian missiles and Topaz, a NATO spy. The inquiry soon spins into a life-threatening escapade of espionage, betrayal and murder.